Theoretical analysis for the downlink spectra efficiency of DS/CDMA cellular systems in rayleigh fadin environment - Pongsatorn Sedtheetorn (2018)
This paper presents an original exact analysis on the downlink spectral efficiency of DS/CDMA cellular systems in Rayleigh fading. We derive a new expression for the probability distribution function of signal to interference plus noise ratio (SINR) which accordingly leads us to propose explicit closed forms of the spectral efficiency and average bit error rate in Rayleigh fading environment. The proposed closed forms are used to accurately investigate the effects of orthogonality, prop-agational condition, and channel noise on the overall efficiency. ©2008 IEEE.